aclimatização e aclimatização de mudas de abacaxizeiro (Ananas comosus L. var. comosus) cv. imperial em substratos orgânicos e comercial - Araújo, Vandeilson Lemos (2018)
The optimization during the acclimatization of plants of pineapple has been promoted through the use of suitable substrates, in order to obtain organic materials with potential use, low cost and easy, resulting in reduced production time, providing with that the seedlings of better quality, pest free and cheaper for subsequent formation of mother nursery ensuring the largest producer stability. Given the above, the objective was to evaluate the growth and development of seedlings of pineapple ‘Imperial’ during acclimatization and acclimatization business and organic substrates. Two experiments were conducted in the Fruit Nursery, DFCA/CCA/UFPB with completely randomized design with four replications, and the experimental unit consisting of 12 seedlings. In the first experiment, the treatments comprised 16 substrate composition, formulated based on a mixture of organic compounds and commercial substrate, corresponding to the acclimatization phase. In the second experiment comprised 15 treatments substrate compositions, corresponding to the acclimatization phase. being obtained by combining composed of crushed cane sugar and chicken manure - CBEA, composed of crushed sugar cane and cattle manure - CBEB, carbonized rice hull - CAC, sand - AL, subsoil - TS and Golden Mix® - GM. In the first experiment evaluated the growth at 90 days after transplanting, determining stem diameter, shoot length, plant diameter, number of leaves, leaf area, leaf dry weight, stem and root; relative shoot/root ratio and leaf area, SPAD index and N-total. In the second experiment the same mixtures of experiment I, except substrate S5 were used, evaluated the growth at 150 days after transplanting in plastic bags, determining stem diameter, shoot length, plant diameter, leaf number, area foliar dry weight, stem and root; relative shoot/root ratio and leaf area ratio, absolute and relative growth, SPAD index, N-total and total chlorophyll.